2019
DOI: 10.1107/s2052252519001568
|View full text |Cite
|
Sign up to set email alerts
|

Structure of mammalian plasma fetuin-B and its mechanism of selective metallopeptidase inhibition

Abstract: Mammalian fetuin-A and fetuin-B are abundant serum proteins with pleiotropic functions. Fetuin-B is a highly selective and potent inhibitor of metallopeptidases (MPs) of the astacin family, which includes ovastacin in mammals. By inhibiting ovastacin, fetuin-B is essential for female fertility. The crystal structure of fetuin-B was determined unbound and in complex with archetypal astacin, and it was found that the inhibitor has tandem cystatin-type modules (CY1 and CY2). They are connected by an exposed linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 79 publications
4
44
0
1
Order By: Relevance
“…In contrast to hydroxyapatite crystals, there were also additional peaks at 1450 and 1670 cm −1 originated from the presence of proteins in the particles. The detected β-sheet amide I peak at 1670 cm −1 was expected for fetuin proteins 37 .…”
Section: Resultsmentioning
confidence: 85%
“…In contrast to hydroxyapatite crystals, there were also additional peaks at 1450 and 1670 cm −1 originated from the presence of proteins in the particles. The detected β-sheet amide I peak at 1670 cm −1 was expected for fetuin proteins 37 .…”
Section: Resultsmentioning
confidence: 85%
“…Specific inhibition of tolloid astacins has been reported for Xenopus laevis sizzled/ogon 31,32 . By contrast, meprins, crayfish astacin, nephrosin from cyprinid fishes, and ovastacin are strongly inhibited by fetuin-B forms from mammals, which are strictly selective for astacins 3336 , and by fish fetuin, which acts as the physiological antagonist of nephrosin 37 . By blocking ovastacin, fetuin-B prevents premature hardening of the zona pellucida and maintains female fertility 26,33,34 .…”
Section: Introductionmentioning
confidence: 91%
“…Within the family, fetuins are type-3 cystatins (subfamily I25C), which include glycosylated proteins with two or three cystatin-like modules 40,41 . Recent crystal structures of the mouse ortholog (mFB), isolated and in complex with crayfish astacin 36 , have revealed that the inhibitor consists of the tandem cystatin-type modules 1 and 2 (CY1 and CY2), which are united by a linker (LNK) with a “CPDCP-trunk” and followed by a C-terminal region (CTR). The inhibitor blocks the active-site cleft of the MP following a novel “raised-elephant-trunk” mechanism 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, serum glycoprotein fetuin‐B, a cystatin superfamily metalloprotease inhibitor that is essential for mouse fertility (Dietzel et al, 2013), was shown to maintain in vitro fertilization by counteracting ovastacin‐mediated cleavage of ZP2 (Dietzel, Floehr, van de Leur, Weiskirchen, & Jahnen‐Dechent, 2017; Dietzel et al, 2013; Floehr et al, 2016). A recent crystallographic study of fetuin‐B and its complex with crayfish astacin, a nonphysiological binding partner that resembles ovastacin, suggested that the function of the inhibitor depends on a rigid disulfide‐linked CPDCP motif located between its two cystatin‐type modules (Cuppari et al, 2019; Figure 2).…”
Section: Cg Exocytosis Modifies the Zp After Fertilizationmentioning
confidence: 99%
“…mediated cleavage of ZP2(Dietzel, Floehr, van de Leur, Weiskirchen, & Jahnen-Dechent, 2017;Dietzel et al, 2013;Floehr et al, 2016). A recent crystallographic study of fetuin-B and its complex with crayfish astacin, a nonphysiological binding partner that resembles ovastacin, suggested that the function of the inhibitor depends on a rigid disulfide-linked CPDCP motif located between its two cystatin-type modules(Cuppari et al, 2019; Figure 2). Activated oocytes and two-cell embryos do not show complete ZP2 cleavage.…”
mentioning
confidence: 99%